MASYARAKAT MULTIKULTURAL (Dinamika Kehidupan Manusia) - Syarqawi, Ahmad (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2018)
Humans as very noble beings have been awarded as inhabitants of the earth and crowned as caliphs (leaders). The role of humans as leaders has given freedom to humans to carry out various creations and innovations that bring benefit to other humans who live hand in hand with themselves. One of the best works of man is human freedom in giving birth to various cultures according to their respective living conditions. This freedom has had an impact on the birth of many cultures that have been built by humans, so that there are often meetings of two or more different cultures. Cultural differences in human life are called multicultural. Thispaper will provide further understanding of human life as an inhabitant of the earth and the attitude that must be displayed in living with other humansoriginating from cultural diversity.Key Word: Multicultural, Human Life